Co‐occurrence of hypertrophic cardiomyopathy and myeloproliferative disorder in a neonate with Noonan syndrome carrying Thr73Ile mutation in PTPN11. (19th August 2015) - Yagasaki, Hideaki; Nakane, Takaya; Hasebe, Youhei; Watanabe, Atsushi; Kise, Hiroaki; Toda, Takako; Koizumi, Keiichi; Hoshiai, Minako; Sugita, Kanji
Abstract : Most cases of Noonan syndrome (NS) result from mutations in one of the RAS‐MAPK signaling genes, including PTPN11, SOS1, KRAS, NRAS, RAF1, BRAF, SHOC2, MEK1 ( MAP2K1 ), and CBL . Cardiovascular diseases of varying severity, such as pulmonary stenosis and hypertrophic cardiomyopathy (HCM), are common in NS patients. RAF1 mutations are most frequent in NS with HCM, while PTPN11 mutations are also well known. Thr73Ile is a gain‐of‐function mutation of PTPN11, which has been highly associated with juvenile myelomonocytic leukemia and NS/myeloproliferative disease (MPD), but has not previously been reported in HCM. Here, we report a Japanese female infant with NS carrying the PTPN11 T73I mutation with NS/MPD, complete atrio‐ventricular septal defect, and rapidly progressive HCM. No other HCM‐related mutations were detected in PTPN11, RAF1, KRAS, BRAF, and SHOC2 . This patient provides additional information regarding the genotype–phenotype correlation for PTPN11 T73I mutation in NS. © 2015 Wiley Periodicals, Inc.